Effect of Structure Parameter on Stress Distribution of Double Helical Tooth Synchronous Timing Belt - Guo Jianhua; Li Shan; Hu Qingming (Jixie chuandong)
The Spiral angle and dislocation quantity is important structural parameters influencing the transmission error,noise and lifespan of the double helical tooth synchronous timing belt. A three dimensional model of double helical tooth synchronous timing belt tooth and pulley under complete meshing is established based on the spatial meshing transmission principle. The hierarchical model of the synchronous timing belt is built concerning with the structural composite material properties. The large deformation and nonlinear static analysis of the above models are conducted with finite analysis software ANSYS Workbench. The results show that there has geometrical distortion deformation of the belt tooth along the lateral direction with the varying stiffness,resulting in maximum stress in the tooth root distributed uniformly along the lateral of the belt tooth and stress concentration in the strengthening layer. Under the same dislocation coefficient,the tooth root stress of the double helical tooth synchronous timing belt with spiral angle of 30° has minimum value,during which the maximum tooth root stress is the smallest.